Modern methods of treatment of post-traumatic bone defects in Department of Trauma Surgery and Emergency Medicine, Medical University of Lublin - Nogalski, Adam; Jojczuk, Mariusy; Lübek, Tomasz; Kucmin, Tomasz; Grabowski, Maciej (Polish Journal of Public Health, 2015)
Motor organ injuries are one of the most common consequences of trauma, out of which comminuted fractures with a bone loss are the most challenging. Numerous methods are applied to treat these injuries; however, still in many cases we are unable to suggest successful medical treatment. Therefore, treating these injuries using elastic and surgically handleable bone replacement materials was started at Trauma Surgery and Emergency Medicine of Medical University of Lublin (provided for the experiments by Medical Inventi Lt). Preliminary assessment based on the results of treatment with bone replacement materials of two patients with comminuted fractures of femur was promising. Bone union was achieved without any adverse effects.